O atual sistema de patentes e a efetivação do direito humano à saúde: uma análise da hanseníase como doença negligenciada, na perspectiva dos vieses da sustentabilidade - Ruviaro, Larissa Melez (2021)
Since the structuring and editing of the legal framework for the patent system, the negligible interest in joint collaboration for the production of medicines was reliably illustrated through its normative model, given that its structural scope disciplined the privileges pertaining to inventors . With these privileges, inventors were allowed to explore their inventions exclusively, that is, an exploratory monopoly was granted to the pharmaceutical industry for a period of twenty years, where in this period it allowed the owner to recover the investment made to improve research and reproduce development . In this way, the patent structure was permeated by the private interests of large multinationals, which strengthened their desire for the manufacture of medicines that enshrine the great potential for profit. This fact directly reflected in the populations affected by neglected diseases due to the lack of economic power, as well as the little profitability verified on the sale of medicines related to these diseases. Thus, it was found that society is segregated by the dictates of the market economy, with regard to accessibility to the treatment of its ailments. Due to this segregation, neglected diseases were not included in the ideals of interest of the large multinational pharmaceutical companies. This directly reflected on leprosy, in view of its social, economic, political and social demerit. While the economic aspect discredited the target population of neglected diseases, through the use of outdated methods and even ineffective medicines under the perverse pretext of lack of innovation. In this context, leprosy was considered a neglected disease, whose incidence reached the apex of its epidemiological profile in Brazil, in the 21st century, while it became a public health problem. Given this finding, it is worth asking whether it is possible to attribute the responsibility for the increase in cases of leprosy in Brazil to the (un)sustainability of the patent system? Thus, the aim of this study is to analyze to what extent the realization of the human right to health is hampered due to the (un)sustainability of the normative model of the patent system, based on leprosy as a neglected disease in Brazil . To achieve the objective, the systemic-complex theory of Fritjof Capra will be used as a base theory, and for the approach the deductive, monographic and historical method. The procedure used to develop this work will be through direct and indirect documentation. Thus, the research technique used will be the elaboration of summaries and records, with the purpose of minimally papyrusing each subject, extracting as much information as possible for the theoretical basis. By way of conclusion, it was concluded that the patent system is unsustainable, under economic and social biases. At the same time, it opposed all the ideas advocated for sustainability, namely: the struggle of countless generations for the realization of human rights and meeting human and social needs, as it propagates the lack of interest in the production of medicine in the face of the populations to which the treatments are intended. For this reason, due to outdated and ineffective treatments, leprosy has returned to show high growth and drug resistance.